Content and language integrated learning (CLIL) on the acquisition of writing skills in secondary education: a systematic literature review - Idris, Faisal; Mohd Said, Nur Ehsan; Sulaiman, Nur Ainil (Intelektual Pustaka Media Utama, 2025)
The concept of content and language integrated learning (CLIL) for English as a foreign language (EFL) writing has been extensively investigated to aid language acquisition; however, there is a paucity of knowledge regarding its impact on a specific element of writing development. This systematic literature review aimed at exploring the impacts of CLIL on EFL writing acquisition in secondary education. Grounded in three databases (i.e., Scopus, Google Scholar, and EBSCO), 43 research articles were extracted from 2015 to 2023 with certain exclusion and inclusion criteria. Findings show that Spain has practiced CLIL the most with various outcomes of specific writing measurement using a range of methods for measuring language through CLIL impacts. However, CLIL shows a dynamic gain in the specific element of writing as it positively impacts all the outcomes of writing measurement. It is suggested that future studies use new techniques for measuring discipline-specific content in writing and focus more on measuring both the language and content dimensions of writing.